‘It’s not that I’m afraid to die…’, - Messham-Muir, Kit (2017)
'I don't want to be there when it happens' shares its title with one of the exhibition's central works by Adeela Suleman, which in turn borrows a line from Woody Allen's 1975 play Death: A Comedy in One Act. The character of Kleinman, a deathobsessed neurotic clearly modelled after Allen himself, suffers a violent death at the hands of an assassin, and as he slips into the abyss is asked if he is afraid of what's coming. He responds: 'It's not that I'm afraid to die, I just don't want to be there when it happens.' It might seem a tenuous link to this exhibition (first seen at Sydney's 4A Centre for Contemporary Asian Art in August, and now in expanded form at the Perth Institute of Contemporary Arts), but the title's origin is pertinent. Throughout Allen's plays and movies, death is an interloper, the subject of neuroses, distanced by humour - repressed, barely, through symbolic means.